Electroluminescent device, mononuclear copper complex guest material and preparation method and application of mononuclear copper complex guest material

By using single-core copper complex materials based on fluorine-containing tridentate phosphine ligand in OLED technology, the problems of high cost of heavy metal materials and environmental pollution are solved, and efficient and low-cost electroluminescent devices are achieved.

CN119823179APending Publication Date: 2025-04-15HEILONGJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510021338.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the existing OLED technology, heavy metal materials are costly and environmental pollution problems. The single-core copper complex is prone to quenching due to structural distortion, and has low efficiency.

Method used

A variety of fluorine-containing tridentate phosphine mononuclear copper complex materials were prepared by changing the number and coordination conditions of fluorine atoms, which were used to prepare efficient evaporation electroluminescent devices.

Benefits of technology

The electroluminescent device with high external quantum efficiency, high brightness and low brightness voltage is achieved, and the photoluminescence performance of the single-core fluorine-containing tridentate phosphine copper complex guest material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823179A_ABST
    Figure CN119823179A_ABST
Patent Text Reader

Abstract

The invention provides an electroluminescent device, a mononuclear copper complex guest material and a preparation method and application thereof, and belongs to the technical field of luminescent materials. According to the mononuclear copper complex guest material, fluorine-containing tridentate phosphine is used as a parent body, different numbers of fluorine atoms are introduced to the parent body, and the mononuclear copper complex is formed through coordination with copper. Various fluorine-containing tridentate phosphine mononuclear copper complex materials are prepared by changing the number of fluorine atoms and different coordination conditions. The rigid mononuclear copper complex synthesized by using the fluorine-containing tridentate phosphine ligand has excellent photoluminescence performance, so that the rigid mononuclear copper complex can be used as a luminescent layer guest material to prepare an evaporation electroluminescent device with high external quantum efficiency, high brightness and low turn-on voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent materials, and in particular to a mononuclear copper complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit, a preparation method of the guest material, an application of the guest material in an electroluminescent device, and an electroluminescent device comprising the mononuclear copper complex guest material. Background Art

[0002] Organic Light Emitting Diode (OLED) is a background-free light source that can be used for lighting and screen display. In the past few decades, the research and development of OLED has never stopped. OLED provides a new and efficient and long-lasting idea for the lighting and display fields, and is gradually replacing the technology on the market. The actual application field is becoming more and more extensive. Especially in the display industry, OLED has become the focus of attention in recent years, because the performance of OLED displays is significantly better than mature technologies such as Liquid Crystal Display (LCD).

[0003] In 1963, Pope et al. first used organic materials to convert electrical energy into light energy, which is considered to be the earliest discovery of electroluminescence. They used silver electrodes as a basis and applied direct current to anthracene single crystals to make anthracene fluoresce. However, this process requires a very high driving voltage (400V), so it cannot be applied in practice. In 1987, Tang and Van Slyke reported the preparation of a double-layer device by using tris(8-hydroxyquinoline)aluminum as the light-emitting layer and the electron transport layer, which was a major breakthrough in the development of OLEDs. When the driving voltage is less than 10V, the external quantum efficiency (EQE) of the green light-emitting device is about 1%. This work broke the obstacles to the development of OLEDs and ushered in a new era. Academia and industry have shown great interest in this pioneering work and have carried out research. According to spin statistics, in OLED devices, the formation of excitons by the recombination of charges (holes and electrons) will produce about 25% singlet excitons (S1) and 75% triplet excitons (T1), but fluorescent devices can only use 25% of S1 to emit light at most. In order to overcome this defect of low device efficiency, Baldo et al. reported an OLED device in 1998. They used fluorescent materials as the main body and red-emitting organic metal complexes as luminescent materials to achieve effective energy transfer from the main body to the guest. At the same time, due to the spin-orbit coupling effect, 100% internal quantum efficiency (Internal Quantum Efficiency, IQE) was obtained, and the reported EQE and IQE were 4% and 23%, respectively. This is a pioneering study of phosphorescent OLEDs. The value of using organic metal complexes as luminescent bodies is that they can achieve 100% IQE by enabling S1 to enter T1 through intersystem crossing (ISC) through strong spin-orbit coupling mediated by heavy metals (such as Ir and Pt) in the complex. However, heavy metal materials are not only expensive, leading to increased costs, but the potential environmental pollution is also a worrying factor. In addition, although the red and green light devices of organic metal materials show excellent performance parameters, the corresponding blue light-emitting materials still need to be improved in terms of device stability, color purity and brightness. In 2012, Adachi and his colleagues first proposed Thermally Activated Delayed Fluorescence (TADF), which ushered in a new era in the research of OLEDs. TADF materials use pure organic small molecules. When the energy level difference between S1 and T1 (Singlet-Triplet SplittingEnergies, ΔE ST) is small enough, the T1 state can pass through the reverse intersystem crossing (RISC) to the S1 state, thereby using the S1 state to emit light, and also achieve 100% IQE. In recent years, OLED display technology has been widely used in the field of small and medium-sized displays, and further development is needed in large-size displays and lighting.

[0004] The structure of OLED devices usually includes a glass substrate, anode and cathode, two injection layers, two transport layers and a particularly important light-emitting layer. Under the applied voltage, the holes generated by the anode and the electrons generated by the cathode pass through the hole injection layer, hole transport layer and electron injection layer, electron transport layer respectively, and finally recombine in the light-emitting layer to form excitons, and the formed excitons return to the ground state through radiation transition to emit light. In addition, the current OLED process preparation commonly used is evaporation and spin coating. Vacuum evaporation forms a dense film by evaporating the material under high temperature and high vacuum. It is suitable for materials with good thermal stability, but the material utilization rate is low and the cost is large. The process is relatively complex and the cost is high, which is not suitable for the preparation of large-area panels. The spin coating process is relatively simple to prepare, suitable for materials with good solubility, high material utilization rate, and suitable for the preparation of large-area panels, but the efficiency and stability of the device are poor. At present, OLED still has some problems, such as short device life, poor stability, and the current high production cost. But we believe that in the near future, these problems will be solved and made more industrialized.

[0005] Of particular interest is that the rich coordination modes and inherent copper-philic interactions of copper complexes produce remarkable luminescent behaviors in the complexes, making them emerging emitters for OLEDs, with rich potential in sustainable display and lighting applications. In 2016, our group reported a tridentate phosphine copper iodide complex named TTPPCuX, which has good thermal stability and rigidity characteristics. The introduced tridentate phosphine ligand has good rigidity. When the copper complex molecules are used to make evaporated devices, the devices can emit yellow light when lit. This work successfully demonstrates the great potential and superiority of copper complexes as optoelectronic integrated systems in various device applications, as well as the significance of ligand engineering. Summary of the invention

[0006] In view of this, in order to solve the technical problems that heavy metals are expensive and pollute the environment, and mononuclear copper complexes are easily quenched in excited states due to structural distortion, resulting in low efficiency, in the first aspect, the present invention provides a mononuclear copper complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit, and prepares a variety of fluorine-containing tridentate phosphine mononuclear copper complex materials by changing the number of fluorine atoms and different coordination conditions. Among them, the rigid mononuclear copper complex synthesized using a fluorine-containing tridentate phosphine ligand has excellent photoluminescent properties, and can therefore be used as a guest material for the light-emitting layer to prepare a vapor-deposited electroluminescent device with high external quantum efficiency, high brightness, and low turn-on voltage.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The mononuclear copper complex guest material is synthesized based on the fluorine-containing tridentate phosphine ligand unit. The fluorine-containing tridentate phosphine is used as a matrix, and different numbers of fluorine atoms are introduced into the matrix to form the mononuclear copper complex guest material through coordination with copper.

[0009] Preferably, the mononuclear copper complex guest material is a compound having the following structural formula:

[0010]

[0011] Among them, R is receptor F.

[0012] Preferably, the mononuclear copper complex guest material is one of the following compounds I to III:

[0013]

[0014] In the second aspect, the present invention provides a method for preparing the above-mentioned mononuclear copper complex guest material based on the synthesis of fluorine-containing tridentate phosphine ligand units, using o-dibromobenzene or p-fluoro-o-dibromobenzene as raw materials and diphenylphosphine to synthesize monophosphine monobromine ligands, which are then reacted with phenyl dichlorophosphine to form phosphine ligands, and finally coordinated with cuprous iodide to prepare the material.

[0015] Preferably, the method specifically comprises the following steps:

[0016] Step (1), adding diphenylphosphine to o-dibromobenzene or p-fluoro-o-dibromobenzene compound to obtain monophosphine monobromine ligand;

[0017] Step (2), adding phenylphosphine dichloride to the monophosphine monobromine ligand prepared in step (1) to obtain a fluorine-containing tridentate phosphine ligand;

[0018] Step (3), adding the fluorine-containing tridentate phosphine ligand obtained in step (2) and cuprous iodide to a solvent, heating for reaction, and obtaining a reaction solution;

[0019] Step (4), post-treating the reaction solution to obtain a mononuclear copper complex guest material.

[0020] Preferably, the reaction temperatures of step (1) and step (2) are -120°C and -78°C, respectively.

[0021] Preferably, the molar ratio of the fluorine-containing tridentate phosphine ligand to the cuprous iodide is 1:(1-12).

[0022] In a third aspect, the present invention provides the use of the mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit in an electroluminescent device.

[0023] Preferably, the mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit is used as a light-emitting layer in the electroluminescent device.

[0024] In a fourth aspect, the present invention provides an electroluminescent device, comprising a light-emitting layer, wherein the light-emitting layer comprises the above-mentioned mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit.

[0025] By changing the number of fluorine atoms and different coordination conditions, a variety of fluorine-containing tridentate phosphine mononuclear copper complex materials are prepared. Among them, the rigid mononuclear copper complex synthesized using the fluorine-containing tridentate phosphine ligand has excellent photoluminescence performance, so it can be used as a guest material for the light-emitting layer to prepare a vapor-deposited electroluminescent device with high external quantum efficiency, high brightness and low turn-on voltage. Compared with the prior art, it has the following beneficial effects:

[0026] (1) The mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit provided by the present invention has good electron transport performance. Different numbers of fluorine atoms can be modified to adjust different luminescent colors, and different electron-withdrawing abilities can adjust the distance between Cu-Cu. At the same time, the tridentate phosphine ligand is used to provide coordination sites to form a copper complex with a rigid structure, which can prepare an efficient vapor-deposited electroluminescent device.

[0027] (2) The electroluminescent peak of the mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit of the present invention is 500-650nm. It is a type of organic copper complex guest material with adjustable luminescent color, which provides a new idea for electroluminescent devices of organic mononuclear copper complex guest materials.

[0028] (3) The fluorine-containing tridentate phosphine mononuclear copper complex guest material in the present invention has good photoluminescence properties. In particular, the external quantum efficiency of the prepared electroluminescent device is the best among the mononuclear fluorine-containing tridentate phosphine copper complex guest materials, and the current efficiency and power efficiency are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The ultraviolet spectrum and fluorescence spectrum test spectra of Examples 1-3 of the present invention;

[0030] Figure 2 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (I) in Example 1 of the present invention are shown;

[0031] Figure 3 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (I) in Example 1 of the present invention are shown;

[0032] Figure 4 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum diagram of the electroluminescent device of compound (II) in Example 2 of the present invention;

[0033] Figure 5 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (II) in Example 2 of the present invention;

[0034] Figure 6 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum diagram of the electroluminescent device of compound (III) in Example 3 of the present invention;

[0035] Figure 7 These are the brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (III) in Example 3 of the present invention.

[0036] Figure 8 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (I) in Example 1 of the present invention are shown;

[0037] Fig. 9 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (I) in Example 1 of the present invention are shown;

[0038] Fig.10 The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum diagram of the electroluminescent device of compound (II) in Example 2 of the present invention;

[0039] Fig.11 The brightness-current efficiency relationship curve, the brightness-power efficiency relationship curve and the brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (II) in Example 2 of the present invention;

[0040] Fig.12The voltage-brightness relationship curve, voltage-current density relationship curve and electroluminescence spectrum of the electroluminescent device of compound (III) in Example 3 of the present invention are shown;

[0041] Fig.13 These are the brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device of compound (III) in Example 3 of the present invention.

[0042] Fig.14 is a single crystal structure diagram of compound (I) in Example 1 of the present invention;

[0043] Fig.15 is a single crystal structure diagram of compound (II) in Example 2 of the present invention;

[0044] Fig.16 The single crystal structure diagram of compound (III) in Example 3 of the present invention is shown. DETAILED DESCRIPTION

[0045] The mononuclear copper complex guest material is synthesized based on the fluorine-containing tridentate phosphine ligand unit. The fluorine-containing tridentate phosphine is used as a matrix, and different numbers of fluorine atoms are introduced into the matrix to form the mononuclear copper complex guest material through coordination with copper.

[0046] In the present invention, the mononuclear copper complex guest material is a compound having the following general structural formula:

[0047]

[0048] Here, R is an acceptor F (fluorine atom).

[0049] Preferably, the mononuclear copper complex guest material is selected from one of compounds I to III:

[0050] When R is a fluorine atom, the compound is (I) (FTTPPCuI);

[0051] When R is four fluorine atoms, the compound is (II) (4FTTPPCuI);

[0052] When R is five fluorine atoms, the compound is (III) (5FTTPPCuI);

[0053] The structural formulas of the compounds are as follows:

[0054]

[0055] The present invention provides a method for preparing the mononuclear copper complex guest material based on the synthesis of the fluorine-containing tridentate phosphine ligand unit, wherein o-dibromobenzene or p-fluoro-o-dibromobenzene is used as a raw material to synthesize a monophosphine monobromine ligand with diphenylphosphine, and then the phosphine ligand is formed with phenylphosphine dichloride, and finally the phosphine ligand is coordinated with cuprous iodide to obtain the guest material.

[0056] The method for preparing the mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit provided by the present invention may specifically include the following steps:

[0057] Step (1), at a temperature of -120 ° C, diphenylphosphine is added to o-dibromobenzene or p-fluoro-o-dibromobenzene to obtain a reaction solution of monophosphine monobromine ligand. Wherein, the temperature is preferably cooled to -120 ° C by mixing n-propanol and liquid nitrogen. After obtaining the monophosphine monobromine ligand, this step (1) may also include a post-treatment operation step. The post-treatment preferably includes extraction, drying and purification. The extraction is preferably to extract the reaction solution with an extractant to obtain an organic layer. The extractant is selected from acetone and dichloromethane, preferably dichloromethane. Drying is preferably to dry the organic layer with a desiccant to remove moisture, and the desiccant is not specifically limited in the present invention, such as anhydrous sodium sulfate. Purification is preferably to purify the dried organic layer by column chromatography, and the eluent of the column chromatography is a petroleum ether solvent.

[0058] Step (2), adding phenylphosphine dichloride to the reaction solution of monophosphine monobromine ligand at -78°C to obtain a fluorine-containing tridentate phosphine ligand;

[0059] Step (3), adding the obtained fluorine-containing tridentate phosphine ligand and CuI to a mixed solvent, heating for reaction, and obtaining a reaction solution; the reaction temperature is preferably 25-65° C., preferably 30-50° C., and more preferably 40-45° C.;

[0060] In step (3), the solvent is selected from amide solvents, such as N,N-dimethylformamide, N,N-dimethylacetamide, aromatic hydrocarbon solvents, such as toluene or xylene, and alkane solvents, such as dichloromethane, chloroform or acetonitrile.

[0061] The molar ratio of the fluorine-containing tridentate phosphine ligand to CuI is 1:(1-12), preferably 1:(2-8), more preferably 1:(4-6), and most preferably 1:6.

[0062] The present invention provides an application of the mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit in an electroluminescent device, especially as a light-emitting layer.

[0063] The present invention also provides an electroluminescent device prepared by using the mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit.

[0064] In the present invention, the electroluminescent device comprises a substrate layer, a conductive anode layer, a hole transport layer, a light emitting layer, an electron transport layer, an electron injection layer and a cathode conductive layer.

[0065] The method for preparing the electroluminescent device provided by the present invention specifically comprises the following steps:

[0066] 1. preparing a conductive anode layer;

[0067] The plastic substrate cleaned with deionized water was placed in a vacuum evaporator with a vacuum degree of 1×10 -6 mbar, and the evaporation rate was set to 0.1 nm s -1 , an anode conductive layer with a thickness of 10 nm and indium tin oxide (ITO) is deposited on a glass or plastic substrate;

[0068] 2. preparing a hole injection layer;

[0069] The hole injection layer material MoO3 is evaporated on the anode conductive layer to obtain a hole injection layer with a thickness of 6 nm;

[0070] 3. Preparation of hole transport layer;

[0071] The hole transport layer material TAPC is evaporated on the hole injection layer to obtain a hole transport layer with a thickness of 50 nm;

[0072] 4. preparing a light-emitting layer;

[0073] A mononuclear copper complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit and a main material mCP are mixed and evaporated on the hole transport layer to obtain a thickness of 20 nm;

[0074] 5. preparing an electron transport layer;

[0075] The electron transport layer material TPBi is evaporated on the light-emitting layer, and the thickness of the electron transport layer is 50nm;

[0076] 6. preparing an electron injection layer;

[0077] The electron injection layer material LiF is evaporated on the electron transport layer, and the thickness of the electron injection layer is 1nm;

[0078] 7. preparing a cathode conductive layer;

[0079] A cathode conductive layer with a thickness of 100 nm and a metal material is evaporated on the electron injection layer to obtain an electroluminescent device. The metal in step seven is aluminum.

[0080] The vapor-deposited electroluminescent device prepared from the mononuclear copper complex guest material provided in the present invention reduces the turn-on voltage to below 3.5V and has good photoluminescent performance, while improving the luminous efficiency and brightness of the organic electroluminescent material, and can prepare an organic electroluminescent diode with excellent performance.

[0081] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.

[0082] Example 1

[0083] In Ar, o-dibromobenzene 10mmol is dissolved in anhydrous ether 50mL and is cooled to -120 ℃.Then, n-butyl lithium 10mmol is added dropwise under agitation.Then, diphenylphosphine chloride 10mmol is added dropwise.Remove cold bath, and the reaction mixture is stirred for another 16 hours.Then, water (50mL) is used to quench the reaction.Mixture is extracted with dichloromethane.Merge organic layer and use anhydrous Na2SO4 drying, remove solvent in vacuo.Purify by flash column chromatography, eluent is PE, obtain monophosphine monobromine ligand.

[0084] In Ar, monophosphine monobromine ligand 10mmol is dissolved in tetrahydrofuran 50mL and cooled to -78 ℃. Then, n-butyl lithium 10mmol is added dropwise under stirring. Then, phenyl dichlorophosphine 5mmol is added dropwise. Remove the cold bath, and stir the reaction mixture for another 16 hours. Then, quench the reaction with water (50mL). The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4, and remove the solvent in vacuo. Purify by flash column chromatography, eluent is DCM: PE (1: 5), and obtain fluorine-containing tridentate phosphine ligand.

[0085] In Ar, 1 mmol of the obtained ligand and 6 mmol of CuI were dissolved in 10 mL of CH2Cl2, and the mixture was heated to 45°C and stirred for 15 hours. The solvent was evaporated to obtain a crude complex, which was then recrystallized from a dichloromethane / n-hexane solution to obtain yellow crystalline FTTPPCuI, which is compound (I).

[0086] The molecular formula of compound (I) is C 42 H 32 P3FCuI was tested with a nuclear magnetic resonance hydrogen spectrometer, and the data are as follows: 1 H NMR (400MHz, CDCl3) δ7.85 (s, 4H), 7.53 (s, 2H), 7.40 (t, J = 7.3Hz, 2H), 7.36-7.23 (m, 11H), 7.20 ( t,J=7.3Hz,2H),7.13(d,J=3.5Hz,2H),7.03(t,J=7.5Hz,4H),6.92(t,J=8.4Hz,2H),6.68(s,4H).

[0087] The obtained compound (I) was tested by UV spectrum and fluorescence spectrum. The test spectrum is as follows: Figure 1 Its single crystal structure is shown in Fig.14 shown.

[0088] The obtained mixture of compound (I) and mCP is used as a light-emitting layer material to prepare an electroluminescent device, and the method is as follows:

[0089] 1. preparing a conductive anode layer;

[0090] The plastic substrate cleaned with deionized water was placed in a vacuum evaporator with a vacuum degree of 1×10 -6 mbar, and the evaporation rate was set to 0.1 nm s -1 , an anode conductive layer with a thickness of 10 nm and indium tin oxide (ITO) is deposited on a glass or plastic substrate;

[0091] 2. preparing a hole injection layer;

[0092] The hole injection layer material MoO3 is evaporated on the anode conductive layer to obtain a hole injection layer with a thickness of 6 nm;

[0093] 3. Preparation of hole transport layer;

[0094] The hole transport layer material TAPC is evaporated on the hole injection layer to obtain a hole transport layer with a thickness of 50 nm;

[0095] 4. preparing a light-emitting layer;

[0096] On the hole transport layer, a tridentate phosphine coordinated mononuclear copper complex electroluminescent dye mixed with the host material mCP is evaporated to obtain a thickness of 20 nm;

[0097] 5. preparing an electron transport layer;

[0098] The electron transport layer material TPBi is evaporated on the light-emitting layer, and the thickness of the electron transport layer is 50nm;

[0099] 6. preparing an electron injection layer;

[0100] The electron injection layer material LiF is evaporated on the electron transport layer, and the thickness of the electron injection layer is 1nm;

[0101] 7. preparing a cathode conductive layer;

[0102] A cathode conductive layer with a thickness of 100 nm and a metal material is evaporated on the electron injection layer to obtain an electroluminescent device. The metal in step seven is aluminum.

[0103] The structure of the electroluminescent device in this embodiment is: ITO / MoO3 (6nm) / TAPC (50nm) / mCP:FTTPPCuI (20nm) / TPBi (50nm) / LiF (1nm) / Al.

[0104] The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are as follows: Figure 2-3 shown.

[0105] Example 2

[0106] In Ar, p-fluoro-o-dibromobenzene 10mmol is dissolved in anhydrous ether 50mL and cooled to -120 ℃. Then, n-butyl lithium 10mmol is added dropwise under agitation. Then, diphenylphosphine chloride 10mmol is added dropwise. Remove the cold bath, and the reaction mixture is stirred for another 16 hours. Then, water (50mL) is used to quench the reaction. The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4. Remove the solvent in vacuo. Purify by flash column chromatography, eluent is PE, obtain monophosphine monobromine ligand.

[0107] In Ar, monophosphine monobromine ligand 10mmol is dissolved in tetrahydrofuran 50mL and cooled to -78 ℃. Then, n-butyl lithium 10mmol is added dropwise under stirring. Then, phenyl dichlorophosphine 5mmol is added dropwise. Remove the cold bath, and stir the reaction mixture for another 16 hours. Then, quench the reaction with water (50mL). The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4. Remove the solvent in vacuo. Purify by flash column chromatography, eluent is DCM: PE (1: 5), and obtain fluorine-containing tridentate phosphine ligand.

[0108] In Ar, 1 mmol of the obtained ligand and 6 mmol of CuI were dissolved in 10 mL of CH2Cl2, and the mixture was heated to 45°C and stirred for 15 hours. The solvent was evaporated to obtain a crude complex, which was then recrystallized from a dichloromethane / n-hexane solution to obtain yellow crystalline 4FTTPPCuI, which is compound (II).

[0109] The molecular formula of compound (II) is C 42 H 29 P3F4CuI, and tested it with a nuclear magnetic resonance hydrogen spectrometer, the data are: 1 H NMR (400MHz, CDCl3) δ7.82 (d, J = 4.5Hz, 4H), 7.40-7.22 (m, 16H), 7.17 (t, J = 7.5Hz, 4H), 6.97-6.88 (m, 2H), 6.82 (s, 4H).

[0110] The obtained compound (II) was tested by UV spectrum and fluorescence spectrum. The test spectrum is as follows: Figure 1 Its single crystal structure is shown in Fig.15 shown.

[0111] An electroluminescent device is prepared using the obtained mixture of compound (II) and CBP as the light-emitting layer material. The method is the same as the method for preparing the electroluminescent device in Example 1, except that the mixture of compound (II) and CBP obtained in Example 2 is used as the light-emitting layer material.

[0112] The structure of the electroluminescent device in this embodiment is: ITO / MoO3 (6nm) / TAPC (50nm) / CBP:4FTTPPCuI (20nm) / TPBi (50nm) / LiF (1nm) / Al.

[0113] The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are as follows: Figure 4-5 shown.

[0114] Example 3

[0115] In Ar, 10mmol of p-fluoro-o-dibromobenzene was dissolved in 50mL of anhydrous ether and cooled to -120°C. Then, 10mmol of n-butyl lithium was added dropwise under stirring. Then, 10mmol of diphenylphosphine chloride was added dropwise. The cold bath was removed and the reaction mixture was stirred for another 16 hours. Then, the reaction was quenched with water (50mL). The mixture was extracted with dichloromethane. The organic layers were combined and dried with anhydrous Na2SO4, and the solvent was removed in vacuo. Purification by flash column chromatography, eluent was PE, and a white powder ligand was obtained.

[0116] In Ar, monophosphine monobromine ligand 10mmol is dissolved in tetrahydrofuran 50mL and cooled to -78 ℃. Then, n-butyl lithium 10mmol is added dropwise under stirring. Then, phenyl dichlorophosphine 5mmol is added dropwise. Remove the cold bath, and stir the reaction mixture for another 16 hours. Then, quench the reaction with water (50mL). The mixture is extracted with dichloromethane. Combine the organic layers and dry with anhydrous Na2SO4. Remove the solvent in vacuo. Purify by flash column chromatography, eluent is DCM: PE (1: 5), and obtain fluorine-containing tridentate phosphine ligand.

[0117] In Ar, 1 mmol of the obtained ligand and 6 mmol of CuI were dissolved in 10 mL of CH2Cl2. The mixture was heated to 45°C and stirred for 15 hours. The solvent was evaporated to obtain a crude complex, which was then recrystallized from a dichloromethane / n-hexane solution to obtain yellow crystalline 5FTTPPCuI, which is compound (III).

[0118] The molecular formula of compound (III) is C 42 H 28 P3F5CuI, and tested it with a nuclear magnetic resonance hydrogen spectrometer, the data are: 1 H NMR (400MHz, CDCl3) δ7.79 (dd, J=10.4, 6.7Hz, 4H), 7.39-7.27 (m, 12H), 7.18 (t ,J=7.5Hz,4H),7.00(t,J=8.0Hz,2H),6.94-6.87(m,2H),6.84(t,J=8.5Hz,4H).

[0119] The obtained compound (III) was tested by UV spectrum and fluorescence spectrum. The test spectrum is as follows: Figure 1 Its single crystal structure is shown in Fig.16 shown.

[0120] An electroluminescent device is prepared using the obtained mixture of compound (III) and mCP as the light-emitting layer material. The method is the same as the method for preparing the electroluminescent device in Example 1, except that the mixture of compound (III) and mCP obtained in Example 3 is used as the light-emitting layer material.

[0121] The structure of the electroluminescent device in this embodiment is: ITO / MoO3 (6nm) / TAPC (50nm) / mCP:5FTTPPCuI (20nm) / TPBi (50nm) / LiF (1nm) / Al.

[0122] The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are as follows: Figure 6-7 shown.

[0123] Comparative Example: The obtained compounds (I)-(III) were used as the light-emitting layer materials to prepare an electroluminescent device. The voltage-brightness relationship curve, voltage-current density relationship curve, electroluminescence spectrum, brightness-current efficiency relationship curve, brightness-power efficiency relationship curve and brightness-external quantum efficiency relationship curve of the electroluminescent device are shown in FIG. Figure 8-13 shown.

[0124] The present invention is described in detail above in conjunction with specific embodiments and / or exemplary examples and drawings, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A mononuclear copper complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit, characterized in that: Taking fluorine-containing tridentate phosphine as the matrix, different numbers of fluorine atoms are introduced into the matrix, and mononuclear copper complex guest materials are formed by coordinating with copper.

2. The mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit according to claim 1, characterized in that: The mononuclear copper complex guest material is a compound having the following structural formula: Among them, R is receptor F.

3. The mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit according to claim 2, characterized in that: The mononuclear copper complex guest material is one of the following compounds I to III:

4. The method for preparing a mononuclear copper complex guest material based on the synthesis of a fluorine-containing tridentate phosphine ligand unit according to any one of claims 1 to 3, characterized in that: The monophosphine monobromine ligand is synthesized with o-dibromobenzene or p-fluoro-o-dibromobenzene as raw materials and diphenylphosphine, and then with phenylphosphine dichloride to form a phosphine ligand, and finally coordinated with cuprous iodide to prepare the product.

5. The method for preparing a mononuclear copper complex guest material based on the synthesis of a fluorine-containing tridentate phosphine ligand unit according to claim 4, characterized in that: The specific steps include: Step (1), adding diphenylphosphine to o-dibromobenzene or p-fluoro-o-dibromobenzene compound to obtain monophosphine monobromine ligand; Step (2), adding phenylphosphine dichloride to the monophosphine monobromine ligand prepared in step (1) to obtain a fluorine-containing tridentate phosphine ligand; Step (3), adding the fluorine-containing tridentate phosphine ligand obtained in step (2) and cuprous iodide to a solvent, heating for reaction, and obtaining a reaction solution; Step (4), post-treating the reaction solution to obtain a mononuclear copper complex guest material.

6. The method for preparing a mononuclear copper complex guest material based on the synthesis of a fluorine-containing tridentate phosphine ligand unit according to claim 5, characterized in that: The reaction temperatures of step (1) and step (2) are -120°C and -78°C, respectively.

7. The method for preparing a mononuclear copper complex guest material based on the synthesis of a fluorine-containing tridentate phosphine ligand unit according to claim 4, characterized in that: The molar ratio of the fluorine-containing tridentate phosphine ligand to the cuprous iodide is 1:(1-12).

8. Use of the mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit according to any one of claims 1 to 3 in an electroluminescent device.

9. The use according to claim 8, characterized in that The mononuclear copper complex guest material synthesized based on the fluorine-containing tridentate phosphine ligand unit is used as a light-emitting layer in the electroluminescent device.

10. An electroluminescent device, characterized in that: The invention comprises a light-emitting layer, wherein the light-emitting layer comprises the mononuclear copper complex guest material synthesized based on a fluorine-containing tridentate phosphine ligand unit according to any one of claims 1 to 3.